Effects of wind turbines on area use and behaviour of semi-domestic reindeer in enclosures - Flydal, Kjetil; Eftestøl, Sindre; Reimers, Eigil; Colman, Jonathan E. (Rangifer, 2004)
In recent decades, industrial developments have expanded into reindeer ranges in the arctic and adjacent higher latitudes in search for energy, minerals, timber and other resources. Several wind turbine parks are under planning in reindeer ranges in Norway, and there is concern about possible negative effects on behaviour and area use of wild and semi-domestic reindeer. We tested whether a wind turbine and its rotor movement had any effect on area use, activity changes, vigilance bouts, and restless behaviour like running, walking, and standing for enclosed semi-domestic reindeer. Five different groups of reindeer in a 450 m long, 8 hectare, enclosure close to a wind turbine were manipulated by turning the wind turbine rotor on and off, and compared with reindeer in a control enclosure without wind turbine exposure. When exposed to rotor movement, two groups used locations farther from the wind turbine, two groups showed no shift, while one group moved closer to the wind turbine. The reindeer showed no systematic differences in the measured behaviour patterns between the two enclosures that could indicate fright or stress as a consequence of the wind turbine or rotor movement. We conclude that semi-domestic reindeer in an enclosure showed no negative behavioural response and little or no aversion towards a wind turbine. The possibility of rapid habituation in a small enclosure with continuous wind turbine exposure suggests that effects on area use should be studied at a larger scale or with free-ranging reindeer. Abstract in Norwegian / Sammendrag: I løpet av de senere tiår har industriell utbygging til utnytting av energi, mineraler, tømmer og andre ressurser ekspandert inn i reinens beiteområder i nordområdene. Flere vindmølleparker er under planlegging i norske reinbeiteområder, og det spekuleres i mulige konsekvenser av disse på atferd og arealbruk hos villrein og tamrein. Vi testet om en vindmølle og dens rotorbevegelse hadde noen effekt på arealbruk, aktivitetsskifter, vaktsomhetsatferd, og rastløshetsatferd i form av løp, gange og ståing for tamrein i innhegning. I en 450 m lang innhegning på 8 hektar som var plassert tett opp til en vindmølle, ble fem forskjellig grupper av reinsdyr manipulert ved å slå vindmøllerotoren av og på. Reinsdyrene i innhegningen ved vindmøllen ble sammenlignet med reinsdyr i en kontrollinnhegning som var uten påvirkning fra vindmøller. Når reinsdyrene ble utsatt for vindmøllerotoren i bevegelse, viste to grupper av dyr et skifte i arealbruk til områder av innhegningen som var lenger unna møllen, to grupper av dyr viste ikke noe skifte i arealbruk, mens en gruppe dyr beveget seg nærmere vindmøllen. Sammenligning av atferden hos reinsdyrene i vindmølleinnhegningen og kontrollinnhegningen viste ingen systematisk forskjell som kunne indikere frykt eller stress som en effekt av vindmøllen eller rotorbevegelsen. Vi konkluderer med at tamrein i innhegning ikke viser negative atferdsresponser og viser lite eller ingen reduksjon i arealbruken tett opp til en vindmølle. Muligheten for at det skjer en rask tilvenning i en liten innhegning der dyrene er i kontinuerlig påvirkning av vindmøllen betyr at effekter på arealbruk bør studeres i et større arealperspektiv eller på frittgående rein.